2012
DOI: 10.2527/jas.2012-5219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed of sire on carcass composition and sensory traits of lamb1

Abstract: This experiment was conducted to compare meat quality and carcass composition of a diverse sampling of sheep breeds. Finnsheep, Romanov, Dorper, White Dorper, Katahdin, Rambouillet, Suffolk, Texel, Dorset, and Composite (½ Columbia rams to 1/4; Hampshire × 1/4; Suffolk) rams were mated to mature Composite ewes. Lambs (n = 804) were reared intensively, grain finished, and serially harvested over a 63-d period. Average harvest age was 216 d and average HCW was 30.7 kg. At a common harvest age, progeny of Suffolk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The IMF data in Shackelford et al (2012) are consistent with data from this study, but they found that Texel-sired lambs had lower slice shear force values than Compositeor Suffolk-sired lambs. Shackelford et al (2012) evalu ated ewe and wether lambs that were harvested in 10 groups from 186 to 249 d of age, whereas we compared Table 5. Allometric growth coefficients (P) and least-squares means, standard error of the mean (SEM), and .P-values for sire breed effects on LM quality measurements at comparable chilled carcass weight only wethers harvested in 3 groups from 201 to 250 d of age; these differences could have affected shear force.…”
Section: Quality Measures With Increasing Time On Feedsupporting
confidence: 88%
See 3 more Smart Citations
“…The IMF data in Shackelford et al (2012) are consistent with data from this study, but they found that Texel-sired lambs had lower slice shear force values than Compositeor Suffolk-sired lambs. Shackelford et al (2012) evalu ated ewe and wether lambs that were harvested in 10 groups from 186 to 249 d of age, whereas we compared Table 5. Allometric growth coefficients (P) and least-squares means, standard error of the mean (SEM), and .P-values for sire breed effects on LM quality measurements at comparable chilled carcass weight only wethers harvested in 3 groups from 201 to 250 d of age; these differences could have affected shear force.…”
Section: Quality Measures With Increasing Time On Feedsupporting
confidence: 88%
“…Genetic correlations calculated by Mortimer et al (2010) indicated that selecting lambs with greater ultra sound LM depth would increase Minolta a* and b* values. Shackelford et al (2012) evaluated quality measures of lambs sired by Composite, Suffolk, and Texel rams. The IMF data in Shackelford et al (2012) are consistent with data from this study, but they found that Texel-sired lambs had lower slice shear force values than Compositeor Suffolk-sired lambs.…”
Section: Quality Measures With Increasing Time On Feedmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolific breeds have more tender meat than terminal breeds. General purpose hair and wool breeds show intermediate values for growth, carcass, and quality traits to terminal and prolific breeds (Shackelford et al, 2012). The most outstanding difference between the breeds on the quality traits, whether the carcass or meat, is the 4.20 6.03 0.37 * ** P < 0.01, *** P < 0.0001, ns = not significant.…”
Section: Discussionmentioning
confidence: 94%